Low voltage four-quadrant current multiplier: an improved topology for n-well CMOS process - Oliveira, Vlademir J. S. [UNESP]; Oki, Nobuo [UNESP] (Springer, 2010)
An analog CMOS current multiplier building block for low voltage applications using an n-well process is presented. The multiplier equations are derived to proof its linear characteristic, and then a low voltage design is proposed. Post layout simulation in a 0.35 mu m AMS CMOS. process and 1.5 V supply voltage shows a THD of 0.84% at 10 MHz and a frequency response bandwidth of 140 MHz.
Keywords: Current multiplier; Low voltage; Symmetrical; Body effect